Motion – Laparoscopic Nissen Fundoplication Is More Cost Effective Than Oral PPI Administration: Arguments for the Motion - Lee L Swanström (Canadian Journal of Gastroenterology)
Gastroesophageal reflux disease is a mechanical disorder of the foregut. While medications can only provide symptom relief, surgery can correct the pathophysiological abnormality of the lower esophageal sphincter. The costs of medical and surgical therapy are much greater than the costs of medication or hospitalization alone. In the case of medical therapy, one must consider the costs of serial monitoring and of failed treatment. The effectiveness of treatment also depends on patient-related factors, including weight, socioeconomic factors, smoking, alcohol use, dietary habits and the use of nonsteroidal anti-inflammatory drugs. Surgical results depend on the experience and skill of the surgeon, as well as the attributes of the institution in which the procedure is undertaken. Therefore, studies that come from specialized centres may not be applicable to the community. Data from the author’s facility indicate that laparoscopic Nissen fundoplication is the most cost effective option when it is undertaken by experienced surgeons on otherwise healthy patients who have documented gastroesophageal reflux disease.